2001
DOI: 10.2174/1381612013397267
|View full text |Cite
|
Sign up to set email alerts
|

Medical Treatment and Neuroprotection in Traumatic Brain Injury

Abstract: The goal of this article is to give an overview about the established current treatment concepts of traumatic brain injury, as well as an outlook on possible future developments in pharmacological neuroprotection. Modern medical treatment modalities of traumatic brain injury (TBI), including the preclinical management of severely head-injured patients, are reviewed. Since an increased intracranial pressure represents the most common complication of severe traumatic brain injury, frequently associated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…Dantrolene has the great advantage that has passed clinical trials, being already in clinical use for treatment of malignant hypertermia, where it decreases body temperature. However, dantrolene ability to counteract hypertermia would not affect its neuroprotective potential, being known that hypothermia is neuroprotective in several acute neurological diseases [47][48][49][50]. It was also reported that hypothermia protects from neuronal cell death induced by KA [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Dantrolene has the great advantage that has passed clinical trials, being already in clinical use for treatment of malignant hypertermia, where it decreases body temperature. However, dantrolene ability to counteract hypertermia would not affect its neuroprotective potential, being known that hypothermia is neuroprotective in several acute neurological diseases [47][48][49][50]. It was also reported that hypothermia protects from neuronal cell death induced by KA [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…7,16 Normally, mitochondria play a major role in the maintenance of intracellular calcium homeostasis. However, when calcium accumulates in the mitochondria after traumatic spinal cord or brain injury, these cell components swell and lose function.…”
mentioning
confidence: 99%
“…16,23,26 Cyclosporin A is believed to exert a neuroprotective effect by blocking the mitochondrial permeability transition pore, inhibiting calcineurin, and thereby preserving mitochondrial function and integrity. 7,8 Another immunosuppressive drug, FK506, which is used to prevent allograft rejection in organ transplantation, has been shown to inhibit calcineurin, reduce accumulation of intracellular calcium from inositol 1,4,5-trisphosphate-sensitive stores, suppress caspase activation, and protect against apoptosis. 5,6,17 The other immunosuppressive drug used in this study, dexamethasone, enhances neurotrophin activity and reduces the proapoptotic expression of c-fos and c-jun.…”
mentioning
confidence: 99%
“…Encouraging therapeutical strategies against secondary brain injury has been investigated in clinical trials 2,10 . However, currently, there is no treatment able to block secondary brain injury and the delayed cerebral atrophy.…”
Section: Discussionmentioning
confidence: 99%